Emotional sound stimuli-related Mismatch Negativities (MMNs) in 3-year-olds in Relation with Prenatal Maternal Depressive Symptoms - Luotonen, Silja (My University, 2021)
Prenatal maternal depression is common in pregnant women and can have negative effects on emotional development in offspring, and even increase children’s risk for mental and behavioral disorders. In toddlers, however, the neural correlates of maternal wellbeing during pregnancy are mostly unknown. In this cross-sectional study, we studied association between the prenatal maternal depression (assessed with Edinburgh Postnatal Depression Scale (EPDS) on the gestational week 24) and the emotional auditory processing of 58 three-year-old children using mismatch negativity (MMN) of the electroencephalogram (EEG). We found that prenatal maternal depression was associated with the emotional MMNs in early time window (80-120ms) in happy emotional category, indicating that children of depressed mothers responded more weakly to happy sounds. However, in sad emotional category (early time window) and in angry emotional category (late time window, 350-450ms) there were no clear associations. This study provided new, valuable information about the relationship between maternal well-being during the pregnancy and the emotional processing in 3-year-olds, a population previously studied only marginally. However, further investigation is called for the modifying role of gender in this relationship.
Keywords: äidin raskaudenaikainen masennus, EEG, herätevaste, tunteiden käsittely